B-line Elastography Measurement of Lung Parenchymal Elasticity. (January 2023) - Koda, Ren; Taniguchi, Hayato; Konno, Kei; Yamakoshi, Yoshiki
This paper proposes a method to determine the elasticity of the lung parenchyma from the B-line Doppler signal observed using continuous shear wave elastography, which uses a small vibrator placed on the tissue surface to propagate continuous shear waves with a vibration frequency of approximately 100 Hz. Since the B-line is generated by multiple reflections in fluid-storing alveoli near the lung surface, the ultrasonic multiple-reflection signal from the B-line is affected by the Doppler shift due to shear waves propagating in the lung parenchyma. When multiple B-lines are observed, the propagation velocity can be estimated by measuring the difference in propagation time between the B-lines. Therefore, continuous shear wave elastography can be used to determine the elasticity of the lung parenchyma by measuring the phase difference of shear wave between the B-lines. In this study, three elastic sponges (soft, medium, and hard) with embedded glass beads were used to simulate fluid-storing alveoli. Shear wave velocity measured using the proposed method was compared with that calculated using Young's modulus obtained from compression measurement. Using the proposed method, the measured shear wave velocities (mean ± S.D.) were 3.78 ± 0.23, 4.24 ± 0.12, and 5.06 ± 0.05 m/s for soft, medium, and hard sponges, respectively, which deviated by a maximum of 5.37% from the values calculated using the measured Young's moduli. The shear wave velocities of the sponge phantom were in a velocity range similar to the mean shear wave velocities of healthy and diseased lungs reported by magnetic resonance elastography (3.25 and 4.54 m/s, respectively). B-line elastography may enable emergency diagnoses of acute lung disease using portable ultrasonic echo devices.